Karakteristik Penderita dengan Infeksi Tuberkulosis di RSUD Sanjiwani - Dewa Ayu Putri Sri Masyeni; Rima Kusuma Ningrum; Ni Kadek Kumara Aida (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2022)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. The incidence of TB in Indonesia (WHO 2018) is the third highest. Meanwhile in Bali, TB cases are increasing by 5% every year. This research is a non-experimental descriptive observational study with a cross sectional design. There are 73 medical record samples (2019-2020) in this study. The results showed that the majority of TB patients were new cases, were of productive age with male gender. There are 34% of patients are active smokers and 13.7% of patients have a family history of tuberculosis infection. There are about 6 patients with anemia and 5 other patients have a history of diabetes. The OAT treatment period, the majority of patients complained of side effects of nausea (64.4%), and dizziness (47.9%) with a success rate of around 78.1%. This research still requires further analysis to find out the relationship between the variables studied.